1998
DOI: 10.1007/s004649900771
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of smoke produced by high-frequency electrosurgery in a closed gaseous environment

Abstract: Electrosurgical smoke produced in a closed environment contains several toxic chemicals. The effects of these on cell viability, macrophage, and endothelial cell activation are not known but are being investigated. Meantime, measures to reduce smoke and evacuate it during endoscopic surgery are advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
109
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 5 publications
3
109
0
6
Order By: Relevance
“…Previous authors have identified chemicals found in electrosurgical smoke. 8 One of the most worrisome is carbon monoxide. During laparoscopic procedures, high levels of CO are produced that can lead to slight elevations of carboxyhemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have identified chemicals found in electrosurgical smoke. 8 One of the most worrisome is carbon monoxide. During laparoscopic procedures, high levels of CO are produced that can lead to slight elevations of carboxyhemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies analysing the chemical composition of surgical smoke have identified up to 80 chemicals, 8,9 including hydrocarbons, nitriles, fatty acids and phenols.…”
Section: Discussionmentioning
confidence: 99%
“…through peritoneum and their penetration into blood and other body fluids [1,2]. The proof of their absorption may be the presence of these compounds or their metabolites in blood and urine.…”
mentioning
confidence: 99%
“…Therefore, analysis of urine samples is an important source of information concerning functioning of the body, as well as its exposure to harmful substances. Whereas smoke production during laparoscopic surgeries is well documented in world literature [1][2][3][4][5][6][7], the analysis of urine samples of patients undergoing laparoscopic procedures in order to assess the potential exposure to such substances has not been performed yet. A number of studies, such as those conducted by Barrett et al [7], show the presence of chemical compounds of different structure and toxicity, which mostly occur in low to trace concentrations, in the smoke produced as a result of tissue thermocoagulation.…”
mentioning
confidence: 99%